Soil Fertility Index of organic, semi-organic, and conventional rice fields on 3 different soil types. Issue 1 (November 2021) - Widijanto, H; Anggastya, D; Syamsiyah, J; Suntoro; Mujiyo
Abstract: In Indonesia, there are three management systems of rice fields, namely organic, semi-organic and conventional. The research aimed to determine the fertility index of rice fields with different management systems on different soil types (vertisol, ultisol, inceptisol). Each combination of the management system and soil type is taken three soil samples as a repetition. The soil parameters analyzed were pH H2 O, total-Nitrogen, available-P, available-K, exchangeable-Ca, exchangeable-Mg, soil organic carbon, Exchangeable-Al, cation exchange capacity, and base saturation. The soil fertility index was determined based on the Minimum Soil Fertility Index (MSFI). Data analysis used was Pearson's Correlation Analysis and Principal Component Analysis (PCA) to determine MSFI. The MSFI values were derived from indicators that have high scores on correlation analysis and PCA. The results showed that the fertility index of rice fields from 3 types of soil ranged from 0.46 to 0.57. Vertisol rice fields have the highest soil fertility index ranging from 0.52-0.57. Conventional management of inceptisol soil has the lowest soil fertility index of 0.46. Vertisol rice fields with organic management with a soil fertility index of 0.57 are the most ideal rice field management system.